Human mast cells stimulate vascular tube formation. Tryptase is a novel, potent angiogenic factor. - Blair, R J (1997)
The presence of mast cells near capillary sprouting sites suggests an association between mast cells and angiogenesis. However, the role of mast cells in blood vessel development remains to be defined. In an attempt to elucidate this relationship, we investigated the effect of human mast cells (HMC-1) and their products on human dermal microvascular endothelial cell (HDMEC) tube formation. Coculture of HMC-1 with HDMEC led to a dose-response increase in the network area of vascular tube growth. Moreover, the extent of neovascularization was enhanced greatly when HMC-1 were degranulated in the presence of HDMEC. Further examination using antagonists to various mast cell products revealed a blunted response (73-88% decrease) in the area of vascular tube formation if specific inhibitors of tryptase were present. Tryptase (3 microg/ml) directly added to HDMEC caused a significant augmentation of capillary growth, which was suppressed by specific tryptase inhibitors. Tryptase also directly induced cell proliferation of HDMEC in a dose-dependent fashion (2 pM-2 nM). Our results suggest that mast cells act at sites of new vessel formation by secreting tryptase, which then functions as a potent and previously unrecognized angiogenic factor.